ABDIMAS KUBU BALI - Gde Bayu Surya Parwita; Ni Nyoman Suryani; Putu Ayu Paramita Dharmayanti (LPPM Universitas Dhyana Pura, 2018)
ABSTRAKKata kunci: Inovasi, Dekorasi, dan laporan keuanganABSTRACTKubu Bali Dekorasi has several problems, namely 1) product presentation, still using paper, so it is prone to damage, 2) There is no information media (stickers, business cards and Instagram) about products from Kubu Bali Dekorasi, 3) financial reports are still written manually , so that there is a risk of errors in making financial reports. From the results of discussions with the Bali Decoration Kubu, it was agreed that several problem solving solutions had been prioritized with several activities of the Science and Technology program that would be applied to the Bali Decoration camp, namely: 1) Provision of Tablets to designate decoration products to prospective customers, directly in terms of making innovations, stickers, business cards and Instagram that contain products of decorating services, 3) assistance with the procedures for preparing financial statements. Currently Kubu Bali Dekorasi has used tablets for product presentations, has stickers, business cards and Instagram to promote their services, and financial reports that have not been done manually.Keywords: Innovation, Decoration, and financial statementsKubu Bali Dekorasi memiliki beberapa permasalahan yaitu 1) Saat presentasi produk, masih menggunakan kertas, sehingga rawan rusak, 2) Belum ada media informasi (Stiker,kartu nama dan instagram) mengenai produk dari Kubu Bali Dekorasi, 3) Laporan keuangan masih ditulis dengan manual, sehingga riskan terjadinya kesalahan dalam membuat lapran keuangan. Dari hasil diskusi dengan pihak Kubu Bali Dekorasi telah disepakati beberapa solusi pemecahan masalah yang telah diprioritaskan dengan beberapa kegiatan dari program Iptek yang akan diterapkan pada Kubu Bali Dekorasi yaitu: 1) Pemberian Tablet guna peruntukkannya untuk presentasi produk dekorasi kepada calon konsumen, 2) Pendampingan secara langsung dalam hal membuat inovasi Stiker, kartu nama dan instagram yang berisikan mengenai produk jasa dekorasi, 3) Pendampingan mengenai tata cara penyusunan laporan keuangan. Saat ini Kubu Bali Dekorasi sudah mempergunakan tablet untuk presentasi produk, memiliki stiker,kartu nama dan instagram untuk mempromosikan jasanya, dan laporan keuangan yan g sudah tidak dikerjakan secara manual.